17β-Estradiol and cathepsins control primordial follicle growth in mouse ovaries. Issue 4 (6th September 2021) - Komatsu, Kouji; Wei, Wei; Murase, Tomohiko; Masubuchi, Satoru
Abstract : This study aimed to clarify the physiological mechanism regulating the growth of primordial follicles in mouse ovaries. In a previous study, we found that increasing the fetal bovine serum concentration in the culture medium promoted the growth of primordial follicles in cultured postnatal day 0 ovaries but not in cultured postnatal day 4 ovaries. Based on these results, we hypothesized that the regulatory system repressing the growth of primordial follicles is established in postnatal day 4 ovaries. To confirm this hypothesis, microarray analysis of postnatal day 0 and 4 ovaries was performed. The results revealed that the expression of mRNA of stefin A homologs increased in postnatal day 4 ovaries. Stefin A belonging to the type 1 cystatin superfamily is an inhibitor of cysteine cathepsins. Consistently, the inhibitor of cathepsins repressed the growth of primordial follicles in cultured postnatal day 0 ovaries. Furthermore, we found that 17β-estradiol promoted the expression of mRNA of stefin A homologs in cultured ovaries and repressed the growth of primordial follicles. Our results demonstrate that 17β-estradiol and cathepsins regulate the growth of primordial follicles in mouse ovaries.